(untitled) (Altre Modernità, 2021)
The purpose of this article is to analyze the collaborative work of Diamela Eltit and Lotty Rosenfeld from Dos guiones, specifically the play "¿Quién viene con Nelson Torres?”. It is a work-installation with pieces of handcrafted video montage that has as its thread the fragmentation of a larger work. As these are the first visual and textual incursions, one can see the beginning of what will be the critical, theoretical and aesthetic setting that Diamela Eltit and Lotty Rosenfeld will develop over the years in various proposals for exhibition and joint work. This article will elaborate a critical proposal of three fundamental aspects for the critique of the image and text in "Who comes with Nelson Torres? Firstly, the politicization of the image will be observed through the montage as a political form of appearance and exhibition. Secondly, we will analyze those figures that remain outside the partition to expose "the unnamed" through a political and aesthetic stance. Finally, the concepts of spatiality and community in the work will be introduced to understand the process of dislocation of the space that is occupied by a multiplicity of singularities that make up a community.